Stereotactic Ablative Radiotherapy for the Treatment of Clinically Localized Renal Cell Carcinoma - Campbell, Scott P. (J Oncol, 2015)
Thermal ablation is currently the most studied treatment option for medically inoperable patients with clinically localized renal cell carcinoma (RCC). Recent evidence suggests that stereotactic ablative radiotherapy (SABR) may offer an effective noninvasive alternative for these patients. In this review, we explore the current literature on SABR for the primary treatment of RCC and make recommendations for future studies so that an accurate comparison between SABR and other ablative therapies may be conducted.